Nanoparticulate Sodium Trimetaphosphate and Fluoride in Gels Affect Enamel Surface Free Energy After Erosive Challenge In Vitro - Díaz-Fabregat, Beatriz [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Ramírez-Carmona, Wilmer [UNESP]; Capalbo, Letícia Cabrera [UNESP]; Báez-Quintero, Liliana Carolina [UNESP]; Sampaio, Caio [UNESP]; Hosida, Thayse Yumi [UNESP]; Monteiro, Douglas Roberto [UNESP]; Pessan, Juliano Pelim [UNESP] (MDPI, 2025)
Background/Objectives: The aim of this study was to evaluate the effects of sodium trimetaphosphate (TMP) and fluoride (F) on the surface free energy (SFE) of enamel coated with human salivary pellicle in vitro, both after treatment with the gels and after an erosive challenge. Methods: Bovine enamel discs (n = 10/group) were randomly allocated into seven treatment groups (gels): placebo (without any actives), low-fluoride gels (4500 ppm F-"4500F") supplemented or not with microparticulate TMP (5%) or nanoparticulate (2.5% or 5%) TMP, 9000 ppm F (positive control), and 12,300 ppm F (acid gel, commercial control); a negative control group (i.e., untreated enamel) was included. Discs were exposed to human saliva (2 h), treated with the gels (1 min) and subjected to a 1-min acid challenge. Three probing liquids were used to assess enamel SFE. Data were submitted to two-way, repeated-measures ANOVA followed by Tukey's test, and by Mann-Whitney's test (p < 0.05). Results: SFE was significantly altered after exposure to saliva, changing from hydrophobic to slightly hydrophilic; gel treatment further increased enamel hydrophilicity (i.e., electron-donor properties), without significant differences among gels. After the erosive challenge, the enamel surface became significantly less hydrophilic for all groups; the highest values were observed for both gels containing nanoparticulate TMP. As for the overall SFE, the best performance was achieved by the gel containing 5% nanometric TMP. Conclusions: SFE of salivary-coated enamel was significantly influenced by the treatment gels, which promoted increases in hydrophilicity. Gels containing TMP, especially at nanoscale, promoted higher resistance to changes in hydrophilicity after an erosive challenge.